Riset Hadis Berbasis Multimedia - Yazofa, Tartila (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
This research discusses multimedia-based hadith research in the reception study of living hadith studies in the form of film media. Muslim individuals in the current era are increasingly exploring religious teachings through social media, especially on YouTube. This phenomenon makes contemporary Muslim scholars convey religious teachings more in the form of video lectures and even package them more interestingly in the form of films that contain Islamic teaching values. Mapping multimedia-based hadith research, one of which focuses on the soap opera "Taqdir Divine Test from Allah" which attempts to portray a model of hadith mediatization packaged in the form of a religious soap opera. This article tries to explain the phenomenon of living hadith receptions presented from multimedia-based hadith research into film shows, including "Papi and Kacung, "The Santri", and "Kaya But Missqueen", the substance of which comes from the words of the Prophet Muhammad Saw. This research uses a qualitative method with direct observation in watching the soap opera film as a primary source and uses a literature study approach as a secondary source regarding topics related to this research. The results of the research show that this research was conducted to examine the trend model for multimedia-based hadith reception in soap operas in Indonesia. This research produces; First, the scenes played by soap opera actors illustrate the hadith in a concrete way so that the wider community can learn from it. Second, soap operas from films perceive hadith exegetically, aesthetically and functionally. Third, the hadith packaged in the form of a soap opera does not fully represent the reality of the hadith, but is sufficient as an alternative for the public to          understand the hadith practically and can be used as a reference as a learning and moral education tool so that the positive values contained in the film can be understood by each individual with Good.